No future for you : salvos from "the Baffler" - Summers, John, 1971-; Lehmann, Chris; Frank, Thomas, 1965- (MIT Press, 2014)
A new collection on carnival hokum and magical thinking in post-apocalypse America -- brought to you by The Baffler.